Islam di Indonesia: Mengusung Demokrasi dengan Basis Budaya - Pranowo, M. Bambang (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2006)
The book begins by looking at the development of democracy in Islamic countries in both the Arab and non-Arab world. One global trend that has become evident following the Cold War, as Azra points out, has been the gradual increase in the numbers of countries that have adopted democracy. This phenomenon is not exclusive to Muslim countries. In this study, Azra cites the report, Freedom in the World 2000: The Democracy Cap, which explains the growth of democracy in lslamic countries in the Arab world where the impact has been quite clear.DOI: 10.15408/sdi.v13i1.579